2010
DOI: 10.1007/s00414-010-0417-9
|View full text |Cite
|
Sign up to set email alerts
|

Odontometric sex assessment from logistic regression analysis

Abstract: Odontometric sex assessment is considered a useful adjunct to more robust predictors such as pelvic and cranial bones, and discriminant function analysis (DA) has been widely applied in dental sex assessment. Logistic regression analysis (LRA) is considered a better alternative, although still untested in odontometric sex prediction. This study examines the use of LRA in dental sex assessment and compares its success to DA. Mesiodistal and buccolingual dimensions of all teeth, except third molars, were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 21 publications
(37 reference statements)
3
38
0
4
Order By: Relevance
“…Under the protection of lips, cheeks, tongue, teeth, bones and dentures, palatal rugae can protect against trauma, high temperature and decomposition, and is less susceptible to trauma and injuries (Shetty et al, 2005;Acharya et al, 2011). In the human lifetime, the length of palatal rugae may change but the location maintains unchanged (Bharath et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Under the protection of lips, cheeks, tongue, teeth, bones and dentures, palatal rugae can protect against trauma, high temperature and decomposition, and is less susceptible to trauma and injuries (Shetty et al, 2005;Acharya et al, 2011). In the human lifetime, the length of palatal rugae may change but the location maintains unchanged (Bharath et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…9,20,22 In our study primary rugae was most commonly observed however did JCMS Nepal 2017;13(2):241-5 Palatal rugae as an indicator of identification not show any significant differences between the genders which is in consistent to the conclusion drawn by Bajracharya et al 10 in Nepalese population, Kapali et al 23 in Austalian Aborigines and Mahabalesh et al 24 in Indian population. Furthermore Acharya et al 25 from a statistical perspective has showed up to 99.2% in identifying gender on analyzing the shape of the palatal rugae. Wavy pattern was the predominant rugae observed in our study which were similar in Australian aborigines, Nepalese and Egyptian population.…”
Section: Discussionmentioning
confidence: 99%
“…Sex determination is an important step in determining the biological profile of unidentified human remains, since a correct result would automatically exclude about half the population in search operations [1]. "Sexual Dimorphism" refers to those differences in size, stature and appearance between male and female that can be applied to dental identification [2].…”
Section: Introductionmentioning
confidence: 99%